Robinson Crusoe - Defoe, Daniel (Italie ELI, 2015)
An adaptation of the classic story about a young man who is shipwrecked on an island. Crusoe eventually meets another person on the island and their friendship leads to his escape and return to the country he left as a young man, almost thirty years before.
Eli Readers is a beautifully-illustrated series of timeless classics and specially-Written stories for learners of English.
Contents. Glossary. Comprehension activities.
Keywords: Adventure; Elementary level; Reading books